Estimación de la disponibilidad y demanda hídrica en la parroquia Sacapalca para su aprovechamiento en el suministro de agua para riego - Nero Gualan, Luis David (2020)
The water resource, is a determining factor in the economic, social and environmental development of the peoples, faces a supply that decreases in the face of a growing demand that occurs because of ensuring food sovereignty for a population. Therefore, the integral management of water resources, which includes access to this resource, becomes one of the main strategies for government agencies, private sectors and community or peasant sectors, in the fight against poverty in the popular sectors of the countryside because, in addition to guaranteeing their subsistence, it reduces productive insecurity and social pressure on highlands. In addition, it allows increasing productivity and enables small-scale production to continue to perform its social function related to the sovereignty and food security of the country. At the same time, the scarce monitoring of hydrographic basins in the province of Loja has caused the lack of hydrometeorological information, which is of fundamental importance for the comprehensive vision of water resource planning. Under these premises, the present work seeks to estimate the water availability in the microbasins of San Ignacio and La Vega, which are of fundamental importance for the development of the Sacapalca parish. Also estimate the demand for water from crops, and compare supply and demand, for irrigation purposes from the perspective of structuring alternatives for the optimization of water resources. The availability of water resources for irrigation purposes was estimated using the rational method, curve number and runoff coefficient criterion, which were implemented through the ArcMap 10,3 software. While the water consumption of the crops was estimated by the Penman Montheith method, automated by the Cropwat 8.0 software, the same one that required the meteorological data of minimum temperature, maximum temperature ° C, relative humidity%, xviii wind speed m / s and heliophany hours / day. It must be emphasized that, since there is no established irrigation zone in the parish, one was defined, considering that it is located below the point of interest determined in each micro-basin, and that it presents the highest concentration of crop areas. Agroecological zoning was carried out in this irrigated area in order to establish territorial zones that allow its sustainable development, through the exploitation of its potentialities. Through agroecological zoning, the category of potential zone for agricultural production was determined, such as the irrigated area, which has an area of 428 ha. Once the irrigation area was determined, a crop pattern was proposed according to the edaphic conditions of the soil, the climatic conditions of the sector and the expertise of the farmers. Finally, through the analysis between supply and demand, it was determined that the water supply of the San Ignacio and La Vega micro-basins covers the demand for the crops proposed for the irrigated area. The same that can be extended to the areas of agrosilvopastoral development and fruit trees, since it was also determined based on the available flow, irrigation method and required flow, which can be increased from 164 ha to the determined 428 ha, by means of sprinkler irrigation, with an efficiency of 75%, or 292 ha through drip irrigation, with an efficiency of 90%. Keywords: Planning, irrigation, efficiency, zoning, sustainable development.